The behavior of aesthetic restoration materials under extreme conditions: in vitro study. - Cerghedi Alessandra-Aniela; Melinda Székely; Cristina Molnar-Varlam ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2022)
Introduction: Aesthetic materials for direct restorations can suffer changes in the oral cavity due to multiple factors acting at this level. The aim of the study was to demonstrate that aesthetic materials undergo structural changes in texture and chemicals, depending on the nature of the extrinsic factor, concentration, and exposure time. Material and methods: We used 3 types of composites, a self-polymerizing composite, two photo-polymerizing composites, and a glass ionomer. 210 teeth were initially immersed in artificial saliva as a control solution and afterwards immersed into artificial gastric juice, ethyl alcohol, energy drink, and distilled water. With the help of a pH meter, we determined the pH of the substances both before and after immersing the teeth in solutions. The teeth were monitored for 24-48 hours in a thermostat bath at 37 degrees Celsius, after which they were analyzed with the help of a rough meter that measures the smallest surface changes. Results: Significant changes in pH occurred in alcohol, where a considerable decrease was observed after 48h. Also, the alcohol produced the most aggressive changes of texture in the composites, and the smallest changes occured in the composite with nanofiller. The glass ionomer was the most affected of all the materials due to the exposure to both alcohol and artificial gastric juice, respectively energy drinks so that the surface analysis could not be performed. Conclusions: The results of the in vitro study are clinically important because the glass ionomer is much too rotten in these extreme situations. Thus, its use is not recommended both in patients with gastroesophageal reflux as well as in alcoholics and persons consuming energy drinks.